The formation mechanism and fluorophores of carbon dots synthesized via a bottom-up route. (7th November 2019) - Qu, Dan; Sun, Zaicheng
Abstract : Carbon dots (CDs) with incomparable optical properties have attracted extensive attention. However, some unclear issues remain, which has impeded the basic understanding and practical application of CDs. Abstract : Carbon dots (CDs) with incomparable optical properties have attracted extensive attention. However, some unclear issues remain, which has impeded the basic understanding and practical application of CDs. The formation process and chemical structure of CDs are critical factors for understanding their optical properties. In this review, recent progress in the formation and fluorophores of CDs is summarized and discussed, which draws a clear picture of related research and indicates a promising future for further studies.